Delayed Disease in Cynomolgus Macaques Exposed to Ebola Virus by an Intranasal Route - Johnston, Sara C.; Wilhelmsen, Catherine L.; Shamblin, Joshua; Kimmel, Adrienne; Zelko, Justine; Wollen, Suzanne; Goff, Arthur J. (Frontiers in Immunology, 2021)
Ebola virus remains a significant public health concern due to high morbidity and mortality rates during recurrent outbreaks in endemic areas. Therefore, the development of countermeasures against Ebola virus remains a high priority, and requires the availability of appropriate animal models for efficacy evaluations. The most commonly used nonhuman primate models for efficacy evaluations against Ebola virus utilize the intramuscular or aerosol route of exposure. Although clinical disease signs are similar to human cases, disease progression in these models is much more rapid, and this can pose significant hurdles for countermeasure evaluations. The objective of the present study was to evaluate the Ebola virus disease course that arises after cynomolgus macaques are exposed to Ebola virus by a mucosal route (the intranasal route). Two different doses (10 pfu and 100 pfu) and delivery methodologies (drop-wise and mucosal atomization device) were evaluated on this study. Differences in clinical disease between dose and delivery groups were not noted. However, a delayed disease course was identified for approximately half of the animals on study, and this delayed disease was dose and administration method independent. Therefore, it appears that mucosal exposure with Ebola virus results in a disease course in cynomolgus macaques that more accurately replicates that which is documented for human cases. In summary, the data presented support the need for further development of this model as a possible alternative to parenteral and small-particle aerosol models for the study of human Ebola virus disease and for countermeasure evaluations.